From Highly Skilled to Low Skilled: Revisiting the Deskilling of Migrant Labor - Sheila V. Siar (Philippine Institute for Development Studies (PIDS), 2013)
Traditional immigration countries such as United States, Canada, Australia, and New Zealand give preference to migrants with higher education, skills, and professional training that they can transfer to their countries. However, it is not unusual for migrant professionals, especially those from less developed countries, to experience 'deskilling' or occupational downward mobility. Though admitted as professionals based on the immigration policies of the destination countries, many of them are relegated to lower status and lower paying jobs, owing to the nonrecognition of their foreign credentials and the bias for education acquired in the host country or in academic institutions in developed countries, local experience, cultural know-how, and English proficiency. Their foreign credentials and skills often fail to provide the expected occupational rewards and professional development gains which have been a significant part of their motivation to migrate overseas, especially to more developed countries.Deskilling may be viewed in several ways: as a host country's way of filling up labor scarcities in the secondary market by exploiting cheap enclave labor, as a transitional phase for migrants to adjust to the 'standards' of the host country, or as a form of institutionalized discrimination. This paper reviews the deskilling phenomenon to highlight its deleterious effects on migrants' welfare. Some theoretical explanations of deskilling are also examined. Examples of deskilling experiences of different migrant groups show that it is a complex phenomenon that demonstrates the interplay of race, ethnicity, and gender.
Keywords: 330; skilled migration; migrant labor; deskilling; job devaluation; brain waste